Development of a digital literacy program for the University of the Philippines Diliman Main Library - Macapugay, Joylyn G. (2015)
This study sought to build a digitally literate community through the library and its services. Digital literacy is a relatively new concept compared to the many other types of literacies that are identified today. Digital literacy encompasses other literacies such as information literacy, ICT literacy, and computer literacy. The academic community is the perfect environment to learn the different types of literacies. Academic institutions that are fortunate to have the latest equipment such as computers, can effectively create an environment that can support digital literacy given that these institutions are also equipped with the proper learning resources such as frameworks and learning modules.